Effect of Heavy Metal Spread on River Flows from Gold Mining Toward Water Biota in Batang Gadis Mandailing Natal River - Yusni Atifah; Fatma Suryani Harahap (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
The purpose of this study is to find out the river water quality in terms of the spread of heavy metals found from the gold mining in Batang Gadis Mandailing Natal River and to determine the effect of heavy metal distribution on river flow from the gold mining of aquatic biota on the Batang Gadis Mandailing Natal River. This research uses descriptive exploratory method by conducting a survey first. Determination of sampling sites using purposive sampling method at the two stations that are determined. Sampling of water and sediments from each location. Water samples were taken as much as 500 mL, samples of sediment were taken at a depth of 10-15 cm from the base surface as much as 100-200 g (Mann, 1978). Examples of water biota are randomly taken at each station as much as 50-100 g, then put together into a composite sample for further analysis in the laboratory. Water quality is measured insitu include temperature, brightness, turbidity, depth, current speed, pH, DO, CO2. While the COD sample, BOD was taken to the laboratory to be analyzed by preservation using ice at a temperature of around 4 oC before observing in the UMTS biology laboratory. Data obtained, then analyzed descriptively. The results of this study are the levels of heavy metals found in the two Batang Gadis River observation stations that are equally good in water, sediment and those found in fish, namely Hg <0,0008, Cd <0,003 and Pb <0,005. Metal levels found are still below the threshold value, but need to be aware of the accumulation of these metals. The histological observations of crisp fish gills at the Bustak mine station are found to experience edema and necrosis which are strongly suspected to be caused by pollution of heavy metals found in the Batang Gadis River. The histological observations of crisp fish liver at the Bustak mine station are found to experience necrosis which is allegedly caused by heavy metal pollution found on the Batang Gadis River